Multiple endometrial polyps is associated with higher risk of chronic endometritis in reproductive‐aged women. Issue 1 (9th December 2020) - Guo, Luyan; Gu, Fang; Tan, Jinfeng; Luo, Lu; Gao, Jun; Zhou, Canquan
Abstract: Aim: To determine whether single endometrial polyp (EP) or multiple EP (polyp number ≥ 6) are associated with chronic endometritis (CE). Methods: From June 2017 to December 2018, this study enrolled a total of 277 patients, including 92 patients with multiple EP, 82 patients with a single EP and 103 patients without polyps who underwent hysteroscopic examination and polypectomy. Polyps and endometrium samples were obtained and subjected to immunohistochemistry for CD138 to identify plasma cells and CE was diagnosed as CD138‐positive plasma cells greater than or equal to 5/high power field. The prevalence of CE was compared and analyzed using the logistic regression model. Results: All baseline parameters were comparable among the three groups except that the prevalence of abnormal uterine bleeding (AUB) was much higher in both polyp groups than the non‐polyp control. The prevalence of CE was significantly higher in the multiple EP group than in the single EP group (58.7% vs 28.0%, P < 0.001). There was no difference on the prevalence of CE between the single EP and the non‐polyp groups (28.0% vs 29.1%, P = 0.872). Multivariable analysis revealed that AUB (adjusted OR 2.81, 95% CI 1.35–5.87) and multiple EP (adjusted OR 2.58, 95% CI 1.38–4.82) were independently associated with CE, while the single EP did not increase the odds of CE compared to the non‐polyp group (adjusted OR 0.74, 95% CI 0.38–1.45). Conclusion: Multiple EP were positively associated with CE among reproductive‐aged women, suggesting a possible hidden etiopathogenetic link between chronic inflammation and multiple EP.